IMPLEMENTASI KEBIJAKAN PENYELENGGARAAN PENDIDIKAN ACEH SESUAI QANUN NOMOR 11 TAHUN 2014 (Studi Kasus Pada Sekolah Dasar Di Kabupaten Aceh Barat) - Lisa Yani; Iskandar Iskandar; Sari Rizki; Hayadin Hayadin; Najamuddin Najamuddin; Hera Yanti (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
The objectives of this research are 1) To determine the forms of implementation of Aceh education implementation policies in accordance with qanun number 11 of 2014 in elementary schools in West Aceh Regency 2) To determine the implementation of Aceh education implementation policies in accordance with qanun number 11 of 2014 in elementary schools in West Aceh Regency 3 ). To find out the obstacles faced in implementing Aceh education implementation policies in accordance with Qanun number 11 of 2014 in elementary schools in West Aceh Regency. This study used descriptive qualitative method. The informants for this research are school principals, school supervisors, class teachers and school committees at State Elementary Schools in Clusters 1, 2 and 3, Woyla District, West Aceh Regency. The research period was from August to September 2023. Data collection techniques used included observation, interviews and documentation. The results of data analysis concluded that the forms of implementation of Acehnese education policy in accordance with Qanun number 11 of 2014 in elementary schools in West Aceh Regency include local content subjects (Acehnese language, tahfiz, reading and writing the Qur'an/Jawo letters, forms of habituation and forms of literacy/calligraphy as well as through the teungkudayah school entry program. Implementation of the Aceh education policy in accordance with qanun number 11 of 2014 in elementary schools in West Aceh Regency is carried out by planning, organizing, carrying out activities and carrying out control/supervision. Planning involves everyone. school components, committees, school supervisors and the surrounding environment and those that were not involved from the start of planning. Organizing includes the organization of curriculum/teaching materials, teacher/teacher organization, schedule time organization, student/class organization and Islamic values/potential organization. environment. Obstacles faced in implementing Aceh education implementation policies in accordance with qanun number 11 of 2014 in elementary schools in West Aceh Regency include internal obstacles and external obstacles. These include the unavailability of specialized Acehnese language teachers, limited budget, no training for teachers in the implementation of Acehnese education such as local content, limited parental support or involvement of school committees, limited facilities and infrastructure and the time available is still using time in the curriculum National is not extra time.